DELEGATIVE DEMOCRACY: CONCEPTS AND UKRAINIAN REALITIES - Romanyuk, О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
This paper is devoted to clarifying the essence of the political regime that emerged in Ukraine as a result of the 2019 presidential and parliamentary elections. The author concludes that the current political regime in Ukraine is a classic example of delegative democracy, as it emerged as a result free, competitive and transparent elections, but after the election all state power was concentrated in the hands of the president, with significant violations of generally accepted standards of democratic of governance and norms and procedures of Ukrainian legislation. He emphasizes that the value of the concept of delegative democracy lies in the fact that it illustrates one of the contradictions in the democratic development of many countries that lack democratic traditions – the contradiction between the electoral legitimacy of government and generally accepted standards of democratic governance. Delegative democracies are by its nature the populist regimes, the emergence of which is caused by the belief of citizens in improving their lives under the leadership of a charismatic person. It is noted that delegative regime as a result of growing public dissatisfaction with both its domestic and foreign policies are democracy has three development trends: 1) comparable endurance; 2) the transformation to autocracy; 3) the removal of the president from power as a result of subsequent elections or mass protests. The author believes that all these alternatives can theoretically be inherent in the current regime of delegative democracy in Ukraine, but the endurance is the least likely of them. The transformation of delegative democracy into autocracy or the elimination of the Zelensky regime as a result of growing public dissatisfaction with both its domestic and foreign policies are more likely.